EVALUASI PROGRAM REVITALISASI PASAR TRADISIONAL PASAR PAGARAN KECAMATAN PAGARAN KABUPATEN TAPANULI UTARA - Lumbantobing, Idauli; Hutahaean, Marlan; Tobing, Artha L (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study discusses the impact of revitalization on traders in the Pagaran market, Pagaran District, North Tapanuli Regency. The research method used is qualitative research. Research data were obtained using interview and documentation techniques. The results of the revitalization show that this market transformation has succeeded in overcoming previous problems. Market cleanliness has increased significantly, existing facilities such as toilets are now better maintained and the construction of new infrastructure has created a more comfortable and safe atmosphere. In addition, the arrangement of sales space and the addition of parking spaces also contribute to increasing the comfort of both buyers and sellers, as well as increasing trader income.